Impact of the Ketogenic Diet on Neurological Diseases: A Review - Carmen Rubio; Alejandro López-Landa; Hector Romo-Parra; Moisés Rubio-Osornio (Life)
Background: The ketogenic diet (KD), high in fat and low in carbohydrates, was introduced in the 1920s as a non-pharmacological treatment for refractory epilepsy. Although its mechanism of action is not fully understood, beneficial effects have been observed in neurological diseases such as epilepsy, Alzheimer’s disease, and Parkinson’s disease. Objective: This review examines the impact of the ketogenic diet and its molecular and neuroglial effects as a complementary therapy for neurological diseases. Discussion: KD is associated with neuroprotective and antioxidant effects that improve mitochondrial function, regulate neurotransmitter flow, and reduce neuroinflammation and oxidative stress. Glial cells play an essential role in the utilization of ketone bodies (KBs) within the central nervous system’s metabolism, particularly during ketosis induced by the KD. Thus, the KD represents a broad and promising strategy that involves both neurons and glial cells, with a molecular impact on brain metabolism and neuroinflammatory homeostasis. Conclusion: Multiple molecular mechanisms have been identified to explain the benefits of the KD in neurological diseases; however, further experimental and clinical studies are needed to address various molecular pathways in order to achieve conclusive results.